Hubungan Pola Asuh Dalam Perspektif Islam Terhadap Kejadian Kecacingan Pada Anak Sekolah Dasar Islam Terpadu (SDIT) Wihdatul Ummah Kota Makassar - Kamariah, Siti; Manyullei, Syamsuar; Bujawati, Emmi (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Helminthiasis is one of the public health problems in Indonesia because its prevalence nature is still quite high, as it is found that children under five and children in primary school (SD) have higher prevalence. Personal hygiene is one of an important factor of the transmission of this disease. This research aims to know the relationship between parenting in Islamic perspective (habit to cut their nails, wash their hands, to use footwear and bowel habits) and the intestinal worms in SDIT Wihdatul Ummah Makassar City. This research is observational analytic study with cross-sectional design. The number of samples as many as 89 people. This samples are chosen by using purposive sampling technique. The results of the study showed that 3.4 percent of respondents, intestinal worms. The results of research also showed that is no significant relationship between the parenting in Islam perspective of helminthiasis in children at SDIT Wihdatul Ummah Makassar City. However, there is a significant relationship between wearing any footwear (p = 0.005) and the intestinal worms in children at SDIT Wihdatul Ummah Makassar City. It is suggested that the need for guidance and providing information media urge people to always wear footwear outside the room. This habit shows a significant relationship toward intestinal worms. Keywords : helminthiasis, parenting in Islamic perspective, elementary school student